Proposed Social Media Marketing Strategy For Improving Sales In Food And Beverage Business Sector - Rahmandi*, Dwinan; Aprianingsih, Atik (Riwayat: Educational Journal of History and Humanities, 2023)
Pietro Coffee was founded on May 1st, 2019 at Trunojoyo Street No 11, Bandung. Pietro takes its name from the icon of a flying squirrel (sugar glider) with the Latin name "Pietromini", which is also the reson wreasonetro took the icon from the sugar glider figure itself. Sugar gliders tend to fly freely from tree to tree. The analogy used by Pietro is to display a unique icon that can spread its wings as wide as possible to expand and always be the center of attention wherever Pietro Coffee is present. The main purpose of Pietro Coffee was formed to accommodate the habits of the Bandung people, who like to hang out with the unique concept that is presented. With a comfortable atmosphere, under the shady and beautiful trees of the city of Bandung while enjoying a cup of coffee in the middle of the city offered by Pietro Coffee. The company's current goal is to grow awareness on digital platforms and gain sales through social media marketing on Instagram, Facebook and Tiktok as their platforms introduce a broad market and sell their products and services as it maximizes positive sentiment in digital channels. This study aims to identify what marketing strategies or activities Pietro Coffee can use to increase its sales. This marketing activity can help Pietro Coffee increase brand awareness, especially in the digital era where Instagram, Facebook and Tiktok can take advantage of the digital era. In this study, the authors will use internal and external analysis of the company using the SWOT matrix, STP analysis, marketing mix, consumer-based brand equity, customer analysis, competitor analysis, and Porter's Five Forces analysis. To do some analysis, the writer uses in-depth interviews to gain insight into the perceptions and motivations of customers in choosing a coffee shop. After conducting several studies that have been stated previously, the authors found that there are gaps owned by Pietro Coffee, especially in terms of marketing. After finding the gaps that Pietro Coffee has, the author tries to solve some of the problems by using TOWS analysis to determine which Pietro Coffee weaknesses and threats can be overcome by optimizing its strengths and opportunities. This analysis generates strategic choices and helps Pietro Coffee discover what strategies can be used to address the problems resulting from relevant WO strategies to answer research questions and achieve objectives. This strategy is a digital marketing focused on Instagram, Facebook and Tiktok providing e- commerce channels for consumer purchasing options to create brand awareness and generate high purchase rates. The author also makes an action plan to provide a better understanding, and this activity will be managed to achieve the target